Earth democracy : justice, sustainability, and peace - Shiva, Vandana (London:. : Zed Books, 2016)
"Calls for a radical shift in the values that govern democracies, condemning the role that unrestricted capitalism has played in the destruction of environments and livelihoods"--
Originally published: Cambridge, Mass. : South End Press, c2005.
Includes bibliographical references and index.
Keywords: Social justice; Environmental justice; Sustainable development; Sustainability -- Political aspects